Assessment of Chemical Quality and Manure Value of Vermicompost Prepared from Mushroom Wastes - Fataei, Ebrahim; Hashemimajd, Kazem (Asian Journal of Chemistry, 2011)
Mushroom wastes are surplus materials, which in spite of their benefit and nutritive value aren't usable for agriculture directly due to high salinity. Thus, these materials are always taken away from production sites. Moreover, the disposal of these materials needs space and facilities in addition to expenses. One of the appropriate methods for the disposal of organic residuals is the production of vermicompost from these wastes. This research was carried out to produce vermicompost from mushroom wastes and to investigate the quality of produced vermicompost in a randomly complete block design with three treatments including wastes of three mushroom factories in four replication and greenhouse condition. The chemical features of mushroom wastes including pH, electrical conductivity, organic carbon, N, P, K, Fe, Cu, Zn and Mn were measured before the experiment. After the production process of vermicompost, some of its quality features including the percentage of moisture, pH, electrical conductivity, organic carbon, N, P, K, Fe, Cu, Zn and Mn were measured. Also, the possibility of using the produced vermicompost in growing of plants was considered. The results of chemical analysis of produced vermicompos, in experimental treatments, were tested statistically using MSTATC and SPSS software. Results indicated that the produced vermicompost had pH buffer with low salinity. Also, the amount of electrical conductivity was decreased considerably in comparison with initial materials. The density of nutritious elements such as N, P and Fe was high in the produced vermicompost. This indicates that this type of vermicompost has appropriate properties that improve soil features and its high manure value ensures the availability of nutritient elements for plants. Overall, the comparison of quality and combination of initial materials and produced vermicompost showed that the produced vermicompost features are to a great extent similar to the produced vermicompost from domestic animals' manure and other plants' residuals. These results show the capacity of the produced vermicompost from mushroom wastes for being used in farms as soil improving materials.